Metabolic Regulation of Immune Responses to Mycobacterium tuberculosis: A Spotlight on L-Arginine and L-Tryptophan Metabolism - Crowther, Rebecca R.; Qualls, Joseph E. (Frontiers in Immunology, 2021)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is a leading cause of death worldwide. Despite decades of research, there is still much to be uncovered regarding the immune response to Mtb infection. Here, we summarize the current knowledge on anti-Mtb immunity, with a spotlight on immune cell amino acid metabolism. Specifically, we discuss L-arginine and L-tryptophan, focusing on their requirements, regulatory roles, and potential use as adjunctive therapy in TB patients. By continuing to uncover the immune cell contribution during Mtb infection and how amino acid utilization regulates their functions, it is anticipated that novel host-directed therapies may be developed and/or refined, helping to eradicate TB.